ANALISIS KEBIJAKAN IMPOR BAN DAN PELUANG BISNIS JASA PUSAT LOGISTIK BERIKAT DI PERUSAHAAN LOGISTIK PT PUNINAR JAYA JAKARTA - Mohamad Farid Nur; Achsanul Nashir (JAMBIS : Jurnal Administrasi Bisnis, 2021)
The Government of Indonesia in March 2016 has officially issued a policy related to BondedLogistics Center (PLB) which is part of the Economic Policy Package Phase II September 2015.The high volume of tire imports in Indonesia makes the government need to develop policies thatregulate the import of tires. So that PLB is expected to be able to regulate the intensity of tireimports in Indonesia which can reduce national logistics costs and reduce dwelling time figures atports and can also bring bonded warehouses, namely PLB, to industry. This can also be anopportunity for Bonded Logistics Center service providers, namely Logistics Entrepreneurswho can play a role in PLB management. This study aims to analyze the extent of thebenefits obtained by PLB service users in terms of time efficiency and logistics costs. Thecomparison between not using PLB and already using PLB is obtained from the survey results withcompanies that have used PLB facilities.